ANALISIS KERJASAMA TIM MEMEDIASI PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA DPRD DI KOTA SOLOK - Ratnawita Ratnawita; Elfiswandi Elfiswandi; Yulasmi Yulasmi (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to determine the influence of competence and work discipline on the performance of the Solok City Regional House of Representatives (DPRD), with teamwork as an intervening variable. The methods used are multiple linear regression analysis and path analysis, with a questionnaire distributed to 92 respondents. The results indicate that there is a positive and significant influence of competence on teamwork in the Solok City DPRD. There is a positive and significant influence of work discipline on teamwork in the Solok City DPRD. There is a positive and significant influence of competence on performance in the Solok City DPRD. There is a positive and significant influence of work discipline on performance in the Solok City DPRD. There is a positive and significant influence of teamwork on performance in the Solok City DPRD. Teamwork is able to mediate the influence of competence on performance in the Solok City Regional Secretariat. Teamwork is able to mediate the influence of work discipline on performance in the Solok City DPRD. Finally, the author recommends that the Solok City DPRD further enhance team cooperation, as it has the most dominant influence on performance in the Solok City Regional Secretariat